Cancer Stem Cell Marker Endoglin (CD105) Induces Epithelial Mesenchymal Transition (EMT) but Not Metastasis in Clear Cell Renal Cell Carcinoma - Junhui Hu; Wei Guan; Libin Yan; Zhangqun Ye; Lily Wu; Hua Xu (Stem Cells International)
Clear cell renal cell carcinoma (ccRCC) is the most common histological subtype of kidney cancer. We previously reported that CD105(+) subpopulation in human ccRCC tumors possesses tumor cell self-renewal and chemoresistance capability. In this study, we showed that CD105(+) ACHN tumor cells exhibit epithelial mesenchymal transition (EMT) phenotype with high expression of mesenchymal marker N-cadherin and low expression of epithelial marker E-cadherin. They are more motile and invasive compared to the unselected parental ACHN tumor cells. The knockdown of CD105 by RNA interference led to the downregulation of N-cadherin and the upregulation of E-cadherin and reduced motility and invasiveness of CD105(+) cells. Overexpression of stem cell factor MYC in CD105 knocked down cells increased mesenchymal markers and cell motility. However, the CD105(+) population of tumor cells does not exhibit an increase metastatic potential in vivo. Findings from this study support that CD105 plays a functional role in maintaining cancer stem cell and EMT phenotype, with MYC as a common mediator for both of these traits. Our work suggests that the ability to metastasize does not coincide with the cancer stem cell or EMT function of CD105.